Analisis Perubahan Frekuensi Motor Listrik Penggerak Pompa Hidrolik Terhadap Well Tractor Performance - Lia Pongsapan; Raditio Rahar; Gunawan Gunawan (Jurnal Teknologi Terpadu, 2024)
Well tractor is a crucial tool in the oil and gas industry that enhances efficiency and productivity. This research aims to analyze the impact of changing the frequency of the electric motor driving the hydraulic pump on the performance of the well tractor. The experimental design involves using a well tractor with an electric motor whose frequency can be varied from 30 Hz to 60 Hz as the independent variable. At the same time, pull force and speed serve as dependent variables. The pull force on the well tractor is measured using a load cell, while speed is calculated using a digital tachometer. The research results indicate a positive and significant relationship between the frequency of the electric motor and the pull force and speed of the well tractor. As the frequency of the electric motor increases, so does the pull force and speed of the well tractor. The increase in pull force on the well tractor is caused by the increase in the rotational speed of the hydraulic pump, which is proportional to the frequency of the electric motor. This research demonstrates that using an electric motor with a higher frequency can enhance the performance of the well tractor. However, it should be noted that increasing the frequency of the electric motor can also lead to higher power consumption. Therefore, an economic analysis is necessary to determine the optimal frequency of the electric motor.